Hadis Prediktif Dalam Kitab Al-Bukhari - Idris, Abdul Fatah (TEOLOGIA, 2013)
Abstract: This studyÂ of predictive hadith in the book al-BukhÄrÄ« give results; first, that all the predictive sanad are sÄ«ngle transmission (aá¸¥ad). The predictive hadith through sÄ«ngle transmission cannot Â be credible when it occurs tadlÄ«s, suspicion and ghairaittiá¹£Äl (not continued). Second, the predictive of matan hadith is a tradition which should not be leaned by the Prophet. However, it is learned by the companions of the Prophet. Is name is mauquf hadith, If is leaned by tabiin or itba tabiin generation, it is called a maqtuâ. The state of validity in matan predictive Hadith, depends on the state of the validity in sanad of Hadith. The state of avoiding disability (âillat) of hadith sanad, is very decisive against the state on the validity of hadith matan, However, Â the state ofÂ validity on the hadith sanad is not necessarily a validity on the hadith matan.Therefore, some of predictive of hadith in book of Sahih al-Bukhari found disability in sanad of Hadith and in matan of hadith. In short, the direct or in direct predictive hadith in the the book of al-BukhÄrÄ« has disability (illat), because it contains the contrary to the Quran, apolitical nature, and theological and dogmatic feud. Abstrak:Â Studi terhadap hadis prediktif dalam kitab al-BukhÄrÄ« ini memberi tiga hasil; pertama bahwa semua sanad predikif itu merupakan transmisi tunggal (aá¸¥ad). Hadis prediktif melalu transmisi tunggal tidak kredibel ketika terjadi tadlÄ«s, kecurigaan, dan ghairaittiá¹£Äl (tidak bersambung). Kedua, bahwa matan hadis prediksi sebuah hadis yang seharusnya tidak di-marfuâ-kan kepada Nabi, tetapi merupakan hadis mauquf yang disandarkan kepada sahabat, dan maqtuâ yang disandarkan kepada tÄbiâÄ«n atau itbaâtÄbiâÄ«n. keadaan krediÂbiÂlitas matan hadis prediksi, tergantung pada keadaan kriteria sanad hadis. Kriteria terhindar dari âillat (cacat) pada sanad hadis adalah sangat menentukan terhadap keadaan kredibiÂlitas matan hadis, tetapi keadaan kredibilitas pada sanad hadis tidak serta merta menjadi kredibilitas pada matan hadis. Sebagian matan hadis prediktif dalam kitab á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ« mempunyai âillat dalam sanad hadis dan âillat dalam matan hadis. Matan hadis-hadis prediksi yang diteliti baik secara langsung maupun tidak langsung adalah mengandung âillat karena bertentangan dengan al-Quran, mengandung hal-hal yang bersifat politis, serta mengandung pertentangan teologis dan dogmatis. Keywords: Hadis, Sunnah, Kriteria,Â Sanad, Matan, dan Prediktif